An Analysis of Artificial Intelligence Integration Among Students: Usage, Impacts, and Educational Implications - Sukarman B; Sri Riski Wulandari; Irfan Arifin; Prusdianto Prusdianto (LP. Ma'arif Janggan Magetan, 2025)
Artificial intelligence (AI) is significantly transforming various aspects of human life, particularly education, by offering diverse features applicable to the learning process. This research aimed to clarify students' AI utilization in learning, explore its impacts and implications, and assess student perspectives on educator preventative strategies against negative effects. Employing a quantitative survey methodology with a cross-sectional design, the study meticulously examined AI integration among students. Data collection involved a six-month preliminary observational phase and the structured online questionnaire. The number of the respondents are 64 of Visual Communication Design students at Universitas Negeri Makassar, with subsequent data analyzed using quantitative descriptive techniques. The findings indicate that most students have adopted AI in their learning. 54% reported rare use, 40% frequent use, and only 3% never used AI. The study identified several negative impacts; 22% of students noted decreased social interaction, 14% observed increased intellectual laziness and reduced creativity, and 13% cited a heightened risk of plagiarism. Additionally, 8% found AI dependence hindered innovative thinking skills, and 6% reported a decline in analytical and critical problem-solving abilities. It is necessary to adjust educational methodologies and curricula to adapt to the diverse implications of AI within the realm of education.